Kajian Revitalisasi Aspek Sosial Pasar Nagari Padang Lua - Alfan Miko; Indraddin Indraddin; Ilham Havivi (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2023)
This article explores the study of market revitalization that needs to be carried out to analyze the socio-cultural and socio-economic aspects of the Padang Lua Nagari market. This study uses qualitative research methods with a case study type. This study was analyzed using the concept of revitalization used by Gouillart and Kelly in Santoso, namely organizational change aimed at spurring corporate growth by aligning the organization with its environment. As a result of this research, it is necessary to revitalize the market. The physical market may not be difficult due to the advancement of development technology today, but what is difficult is to make the market better and not cause conflict between the relevant stakeholders. The conclusion of this research is to accommodate the revitalizing of the market, an in-depth study of aspects of spatial planning so that a quality and beneficial market for the community can realized.